Seeing the forest but not the trees: Heterogeneity in community size effects in Canadian ice hockey players - Wattie, N.; Schorer, J.; Baker, J. (Journal of Sports Sciences, 2018)
The community size effect (or birthplace effect) suggests that high-performance athletes are less likely to emerge from regions with population sizes that are very small or very large. However, previous research on elite Canadian ice hockey players has not considered the influence of intra-national regional variation of population distributions with respect to community size effects. Therefore, the purpose of the current study was to test the heterogeneity of the community size effect between Canadian National Hockey League draftees (2000-2014: n = 1505), from 7 provincial regions within Canada (i.e., British Columbia, Alberta, Saskatchewan, Manitoba, Ontario, Quebec and the Atlantic Provinces). The proportion of athletes in the 9 census population categories were compared to the national and regional general population distributions in the census categories. Results suggest variability of community size effects between the 7 provincial regions within Canada, with only the province of Ontario demonstrating a community size effect congruent with effects reported in previous research. Using regional general population distributions as the comparator to athlete populations changed the direction, meaningfulness and magnitude of community size effects. In conclusion, elite ice hockey player community size effects may not be generalisable to all regions within Canada.